Upaya Peningkatan Pengetahuan Siswa Terhadap Dampak Positif dan Negatif Penggunaan Media Sosial - Mas Intan Purba; Nina Purnasari; Dhita Adriani Rangkuti; Wirda Lilia; Demak Claudia Yosephine Simanjuntak (KALANDRA Jurnal Pengabdian Kepada Masyarakat, 2023)
The development of social media with various features that can be accessed anywhere has made more and more social media users from various backgrounds such as teenagers. The use of social media with its various impacts needs to be socialized to adolescents because currently social media has positive and negative impacts on physical and mental health. The general objective of this community service activity is to find out an overview of youth's knowledge about the positive and negative impacts of using social media for mental health. The methods in this community service activity are: 1. Analysis of the community situation. This stage can be carried out with two sub-stages, which are further divided into several possibilities. First: determine the target audience, Second: determine the problem areas to be analyzed. 2. Problem identification. The results of the analysis work which includes the objectives and problem areas mentioned earlier are that the problems faced by the selected target group can be identified and then formulated. 3. Define specific work goals, in other words what changes are desired. 4. Problem solving plan. Problems that have been identified need to be solved. 5. Social approach. What is meant is the approach to the target community. 6. Implementation of activities. 7. Evaluation of activities and results. Suggestions for schools are to include activities to increase youth knowledge about social media, positive and negative impacts of using social media in the school's extracurricular schedule. This can be done in groups/peer groups with selected social media ambassadors